Latest Digitalisation Initiatives and Challenges in Cross-Border Labour Mobility in the European Union – “Fit for the Future”? - Marcin KIEŁBASA (Communications of International Proceedings, 2025)
This study examines recent European Union initiatives aimed at digitalising the governance of cross-border labour mobility, focusing in particular on the Entry/Exit System (EES), the Electronic Exchange of Social Security Information (EESSI), and the emerging European Social Security Pass (ESSPASS). The motive behind the study lies in the EU’s growing reliance on digital tools to enhance administrative efficiency, transparency, and legal certainty in an increasingly mobile labour market. Despite these ambitions, the literature has not yet sufficiently addressed how these digital systems interact, what challenges they face in practice, and how uneven digital capacities across Member States may hinder the realisation of a seamless mobility framework. This gap is especially relevant as the EU transitions from paper-based procedures to interoperable, cross-sectoral digital infrastructures. Methodologically, the study employs legal and institutional analysis of the systems’ regulatory foundations, operational designs, and implementation trajectories. It draws on EU legislation, Commission communications, and practical evaluations of ongoing pilot projects to assess the coherence and feasibility of these instruments. The findings show that while initiatives such as the EES and EESSI offer significant potential to streamline border management and social security coordination, their success depends on overcoming barriers related to interoperability, data protection, institutional fragmentation, and differential digital readiness. The analysis concludes that digitalisation in this domain constitutes not merely a technical reform but a broader governance challenge whose success requires sustained political commitment and inclusive implementation across the Union.
Keywords: digitalisation; European Union; labour mobility; Entry/Exit System (EES); EESSI; ESSPASS